Integrated Assessment of sustainable roofing technologies for urban heat island mitigation: a data-driven case study in Nantong, China - Francis Deng Clement; Jiang Yan; Shutian Zhou (Journal of Asian Architecture and Building Engineering)
This study evaluates eco-friendly roof systems’ potential to mitigate the summertime urban heat island (UHI) effect in Nantong City, China, using an optimized, Python-based energy balance model. Unlike previous single-technology analyses, this research integrates dark membrane, high-albedo, green, and solar-integrated roofing options into one model, leveraging in-situ meteorological and field data from similar coastal cities for local accuracy. Dark membrane and black PV-covered roofs showed the highest peak sensible heat fluxes (320–400 W/m2). While PV panels slightly increased peak flux, they reduced total sensible flux from black roofs by 12%. Converting black membrane roofs to cool (high-albedo) or green roofs decreased the total sensible flux by 48%. Integrating solar panels atop reflective or green roofs achieved a 60% reduction, demonstrating optimal cooling and renewable energy generation. This is the first quantified evaluation of PV-integrated roofing solutions in Nantong’s urban climate, offering a novel framework for modeling heat flux interactions. The findings provide a data-driven basis for UHI mitigation, sustainable urban planning, and offer recommendations for optimizing roof designs in Chinese coastal cities, promoting long-term urban resilience.